Global Attractivity of a Higher-Order Difference Equation - R. Abo-Zeid (Discrete Dynamics in Nature and Society)
The aim of this work is to investigate the global stability, periodic nature, oscillation, and the boundedness of all admissible solutions of the difference equation xn+1=Axn-2r-1/(B-C∏i=lkxn-2i), n=0,1,2,… where A,B,C are positive real numbers and l,r,k are nonnegative integers, such that l≤k.